Theileria annulata Subtelomere-Encoded Variable Secreted Protein-TA05575 Binds to Bovine RBMX2 - Li, Zhi; Liu, Junlong; Zhao, Shuaiyang; Ma, Quanying; Liu, Aihong; Li, Youquan; Guan, Guiquan; Luo, Jianxun; Yin, Hong (Frontiers in Cellular and Infection Microbiology, 2021)
Tropical theileriosis is the disease caused by tick-transmitted apicomplexan parasite Theileria annulata, which has ability to transform bovine leukocytes, including B cells, macrophage cells, and dendritic cells. The T. annulata transformed cells are characterized as uncontrolled proliferation and shared some cancer-like phenotypes. The mechanism of the transformation by T. annulata is still not understood well. In previous reports, the subtelomere-encoded variable secreted proteins (SVSP) of T. parva were considered to contribute to phenotypic changes of the host cell, but the role of SVSP of T. annulata in host-pathogen relationship remains unknown. In the present study, a member of SVSP family, TA05575 of T. annulata was selected as the target molecule to analyze its expression profiles in different life cycle stages of T. annulata by qPCR and investigate its subcellular distribution of different passages of T. annulata transformed cells using confocal experiments. From the results, the transcription level of TA05575 at schizont stage was significantly higher than the other two life stages of T. annulata, and the protein of TA05575 was mainly distributed in nucleus of T. annulata infected cells. In addition, the potential proteins of host cells interacting with TA05575 were screened by Yeast-two hybrid system. The results of Co-IP experiment confirmed that TA05575 interacted with RBMX2-like protein that participated in transcription regulation of cells. In addition, a novel BiFC assay and flow cytometry were carried out, and the results further revealed that TA05575-RBMX2-like pair was directly interacted in cell context. Moreover, this interacting pair was found to distribute in intracellular compartments of HEK293T cells by using confocal microscopy. The results of the present study suggest that TA05575 may contribute for cells transformation due its distribution. According to the function of RBMX2, the interaction of TA05575 and RMMX2-like will provide a new information to further understand the mechanisms of cells transformation by T. annulata.